Cross-Reactive Immunity to Clade 2 Strains of Influenza Virus A Subtype H5N1 Induced in Adults and Elderly Patients by Fluval, a Prototype Pandemic Influenza Virus Vaccine Derived by Reverse Genetics, Formulated with a Phosphate Adjuvant, and Directed to Clade 1 Strains - Fazekas, György; Martosne-Mendi, Rita; Jankovics, Istvan; Szilvasy, Istvan; Vajo, Zoltan (Clinical and Vaccine Immunology, 2009)
Classifications Services CVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue CVI About CVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy CVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 1556-6811 Online ISSN: 1556-679X Copyright © 2014 by the American Society for Microbiology. For an alternate route to CVI .asm.org, visit: CVI